Intersecções entre pensamento literário e pensamento filosófico em Gilles Deleuze ou Riobaldo e seu gosto de especular conceitos no Grande Sertão: Veredas - Barroso, Lucca Fernandes (2025)
The present dissertation intends to explore the zones of indiscernibility and proximity between philosophy and literature. It aimed to design, following Gilles Deleuze, the mode in which that which concerns the philosophical creation, namely concepts, can be found in a literary work, Grande Sertão: Veredas. The text is thus divided in three sections, in three articles that can be read isolated but which form together a cohesive whole. In a first moment, there’s an article which intends to demonstrate Deleuze’s understanding of the intersection and exchange between artistic thought and philosophical thought, as systematized in O que é a filosofia?, indicating, following Deleuze and Guattari, the creative specificities — and, thus, their respective constructivisms — of philosophy and art, while subsequently indicating its echoes and shared elements; the second text is devoted exclusively to examining Deleuze's comprehension of literature, addressing the following themes which are at the heart of it: the creation of health, the foreignness of language, the people yet to come and intensive writing; finally, the third text is dedicated to sketching the first traces of what I have called “riobaldian concepts”, identifying terms which are employed by Riobaldo throughout his narration in Grande Sertão: Veredas and which, although presented in a literary novel, can be conceived as philosophical concepts insofar as they’re terms which condense a series of components that aims to address problems concerning the very life of the character-narrator